Development and validation of assessment instrument for school students in prison in Malaysia - Nuraihan Mohamad Hashim; Muhamad Suhaimi Taat (Human Resource Management Academic Research Society, 2022)
The purpose of this study was to develop and validate an instrument to assess the occurrence of students in schools in prisons in Malaysia. Based on the literature review and sharing sessions with experienced teachers who teach in prison schools, the researcher identified constructs and items that contribute to the measurement of student achievement. Validity and reliability have been done on the constructed items. The content validity of this instrument involved 8 experts in various fields. A total of 432 students were involved in this study. As a result, a newly developed instrument consists of 4 constructs of student development which are attitude, achievement motivation, morals and academic self-efficacy. Exploratory factor analysis was conducted to obtain construct validity using SPSS software. The factor loading of each item is in the range of 0.669 to 0.805 and the reliability value (alpha) is in the range of 0.78 to 0.83. The total number of items built based on the construct is 55 items. The findings of this study clearly show that this instrument has high validity and reliability and can be used to assess the performance of students in schools in prisons in Malaysia.